IMPLEMENTASI BAHASA ARAB DALAM KEGIATAN HARIAN DI TPQ AL-KAUTSAR KAYEN PACITAN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of Arabic in daily activities at TPQ Al-Kautsar Kayen Pacitan based on observation data and interviews with teachers. This research is motivated by the importance of learning Arabic from an early age as a foundation for understanding Islamic teachings and efforts to improve the linguistic competence of students through a habituation approach. The research uses a descriptive qualitative approach to describe the phenomenon systematically and factually according to field conditions. The data collection technique was carried out through direct observation of learning activities and semi-structured interviews with three teachers, namely Syaifullah, Zainal Abidin, and Ahmad Syahroni. Observations were focused on the use of Arabic in daily activities, teaching methods, and student responses and skill development. Data is analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study showed that the implementation of Arabic was carried out through the habit of opening and closing greetings, daily prayers, simple expressions, and class instructions in Arabic. The methods used include memorization of mufradat, drilling, simple questions and answers, and educational songs and games to increase learning motivation. The response of the students tends to be positive, characterized by an increase in mastery of basic vocabulary, understanding the meaning of prayer, and courage in having simple conversations. The main obstacles are differences in students' abilities and limited learning time, which are overcome through regular repetition, individual approaches, and the application of cooperative learning between students. This study concludes that the habituation of Arabic in daily activities in a consistent and structured manner is effective in improving the basic Arabic language skills of TPQ Al-Kautsar students, especially in terms of vocabulary and courage to speak. This implementation has the potential to become a habituation-based Arabic learning model in other non-formal educational institutions.